2021
DOI: 10.48550/arxiv.2109.03960
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Rates of convergence to non-degenerate asymptotic profiles for fast diffusion via energy methods

Abstract: This paper is concerned with a quantitative analysis of asymptotic behaviors of (possibly sign-changing) solutions to the Cauchy-Dirichlet problem for the fast diffusion equation posed on bounded domains with Sobolev subcritical exponents. More precisely, rates of convergence to non-degenerate asymptotic profiles will be revealed via an energy method. The sharp rate of convergence to positive ones was recently discussed by Bonforte and Figalli [10] based on an entropy method. An alternative proof for their r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…(iv) In the subcritical regime, Bonforte-Grillo-Vázquez [8] proved the uniform convergence of the relative error, and Bonforte-Figalli [7] proved the sharp exponential decay of the relative error on generic domains; see Akagi [1] for another proof. In our recent papers [37,38], we proved the sharp exponential decay of the relative error in the C 2 topology on generic domains, and polynomial decay of the relative error in the C 2 topology on all smooth domains.…”
Section: Introductionmentioning
confidence: 93%
See 2 more Smart Citations
“…(iv) In the subcritical regime, Bonforte-Grillo-Vázquez [8] proved the uniform convergence of the relative error, and Bonforte-Figalli [7] proved the sharp exponential decay of the relative error on generic domains; see Akagi [1] for another proof. In our recent papers [37,38], we proved the sharp exponential decay of the relative error in the C 2 topology on generic domains, and polynomial decay of the relative error in the C 2 topology on all smooth domains.…”
Section: Introductionmentioning
confidence: 93%
“…In the pioneering work [6], Berryman and Holland studied the extinction behavior of solutions to the Cauchy-Dirichlet problem (1)- (3). Their work was motivated by the Wisconsin octupole experiments of Drake-Greenwood-Navratil-Post [31] on anomalous diffusion of hydrogen plasma across a purely poloidal octupole magnetic field, where the density of the plasma satisfies the fast diffusion equation (1) with p = 2. The experiments in [31] have shown that after a few milliseconds the solution u evolves into a fixed shape which then decays in time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Their derivation was subsequently simplified by Agaki [2], though the comparison of his bounds in terms of an energy rather than the relative error exploits Jin and Xiong's recent boundary regularity theory [19]. On arbitrary smooth domains, however, the kernel is not necessarily trivial, hence the limiting stationary solution is in general not isolated, and thus, the proposed method is not applicable.…”
Section: Introductionmentioning
confidence: 99%